Literature Review of Islamic Cultural History Learning Media on the Implications of Contextual Learning in Madrasah - La Jusu; Maudin; Madi (AIQU: Journal Multidiscipliner of Science, 2025)
The subject of Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) holds a strategic position in madrasah education, as it not only conveys historical knowledge but also instills values, shapes character, and strengthens Islamic identity. However, SKI learning at the Madrasah Aliyah level still faces challenges, particularly in the use of conventional media that lack contextual relevance to the needs of 21st-century learners. This study aims to identify the types of instructional media that have been used in SKI teaching and evaluate their relevance to the pedagogical needs of madrasah students. The method employed is a systematic literature review (library research) with a qualitative approach using thematic analysis of scholarly sources published over the past ten years. The study identified three key media types that are both relevant and effective: audiovisual media (films), question cards, and the Canva application. These media have been found to enhance student engagement, strengthen historical understanding, and integrate Islamic values into learning in a contextual and engaging manner. This study recommends the development of SKI instructional media that is adaptive to digital literacy, value-based, and aligned with the characteristics of madrasah students, thereby promoting more transformative and meaningful learning.